Press Enter

Share with your friends and help them crack UPSC!

Or Share on

Answer

Correct Option is 12

Solution:Using step 4 in second row 25-2= 23
second row becomes = 23 6
Similarly using step 1 in second row 23-6=17
So, the resultant of second row =17
Hence value of X=17
Now, applying step 4 in first row becomes=17-4=13
So, the first row becomes 13 18
Using step 1 resultant of first row= 18-13=5
So, the difference of the resultant of the two rows=17-5=12

Get access to all of our verified questions